IMPLEMENTASI PROGRAM MUHADHARAH SEBAGAI UPAYA MENINGKATKAN SIKAP PERCAYA DIRI SISWA KELAS XI AGAMA DI MAPM CUKIR JOMBANG - Fadilla, Witri Nur; Umam, Khoirul (PAI FAI UNHASY Tebuireng Jombang, 2024)
This article describes an analysis regarding the implementation of the muhadharah program which is an effort to increase student self-confidence. This research is a qualitative research with a case study type. The data obtained in this study is through direct observation, interviews and documentation of the results. The existing data is then reduced, then presented, and verified. The results of this study indicate that (1) At MAPM Cukir Jombang there is a muhadharah program focused on lecture activities which are carried out every day before the Dhuha prayer in rotation according to the class on duty. (2) The implementation of the muhadharah program at MAPM Cukir Jombang is one of the mandatory activities that can train self-confidence to appear in public, which is carried out in stages: preparation, implementation and evaluation. (3) the muhadharah program at MAPM Cukir Jombang can train students' self-confidence to appear in public and then hone students' communication skills when speaking in front of a crowd.